Объяснение:
в) -3x(0,6x-12)=0
-3x=0 0,6x-12=0
x1=0 0,6x=12
x2=20
г) (5-2t)(7+5t)=0
5-2t=0 7+5t=0
2t=5 5t=-7
t1=2,5 t2=-1,4
д) (y-3)(y+4)(3y-5)=0
y-3=0 y+4=0 3y-5=0
y1=3 y2=-4 3y=5
y3=1 2/3
e) 5z(z+1)(3z-17)=0
5z=0 z+1=0 3z-17=0
z1=0 z2=-1 3z=17
z3=5 2/3
ж) t^4=0
t=0
з) (3x+2)^2=0
3x+2=0
3x=-2
x=-2/3
и) x^2(x-3)(x+6)=0
x^2=0 x-3=0 x+6=0
x1=0 x2=3 x3=-6
к) y^3(y-1)^2(y+1)=0
y^3=0 (y-1)^2=0 y+1=0
y1=0 y-1=0 y3=-1
y2=1
-4x⁴ + 5x² - 1 = 0
4x⁴ - 5x² + 1 = 0
Пусть t = x², t > 0
4t² - 5t + 1 = 0
D = 25 - 4·4 = 9 = 3²
t₁ = (5 + 3)/8 = 1
t₂ = (5 - 3)/8 = 2/8 = 1/4
Обратная замена:
x² = 1 и x² = 1/4
x = -1 и 1 и -1/2 и 1/2.
ответ: x = -1; -1/2; 1/2; 1.